2018
DOI: 10.1016/j.jcin.2018.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management, and Associated Clinical Outcomes of New-Onset Atrial Fibrillation Following Transcatheter Aortic Valve Replacement

Abstract: Post-TAVR AF occurred in 8.4% of patients (4.4% with TF access, 16.5% with non-TF access), with fewer than one-third of patients receiving anticoagulation at discharge, and was associated with increased risk for in-hospital and 1-year mortality and stroke. Given the clinical significance of post-TAVR AF, additional studies are necessary to delineate the optimal management strategy in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 29 publications
4
56
0
Order By: Relevance
“…13 BMI, AF, and low serum albumin level have all been discussed previously as predictors of death in TAVR patients. [14][15][16] Nonetheless, this is the first study to demonstrate the effect of TAVR risk score on mid-term outcomes following TAVR.…”
Section: Discussionmentioning
confidence: 88%
“…13 BMI, AF, and low serum albumin level have all been discussed previously as predictors of death in TAVR patients. [14][15][16] Nonetheless, this is the first study to demonstrate the effect of TAVR risk score on mid-term outcomes following TAVR.…”
Section: Discussionmentioning
confidence: 88%
“…analysis from the TVT Registry has established a similar association between postoperative atrial fibrillation and post-TAVR stroke. 24 Other studies have identified cardioembolic events from the left atrial appendage as a potential mechanism of post-TAVR stroke. 25,26 Strategies to mitigate post-TAVR stroke in patients with atrial fibrillation are needed given that atrial fibrillation is a frequent comorbidity in TAVR candidates.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Strategies to mitigate post-TAVR stroke in patients with atrial fibrillation are needed given that atrial fibrillation is a frequent comorbidity in TAVR candidates. 24 Although this study did not identify a protective association with oral anticoagulant and 30-day neurologic risk, this analysis included both patients with and without atrial fibrillation with indications for oral anticoagulant therapy, so the association with oral anticoagulant therapy and 30-day post-TAVR stroke in patients with atrial fibrillation was not specifically examined. The WATCH-TAVR Trial (NCT03173534) is currently testing a strategy of TAVR with concomitant percutaneous left atrial appendage closure in patients with atrial fibrillation, which is a novel nonpharmacologic strategy to mitigate stroke risk after TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] New-onset AF after transfemoral (TF)-TAVR occurs in 4.4% of patients and substantially increases mortality risk. 10,11 AF is a strong predictor of thromboembolic events, but the benefits of anticoagulation therapy require careful balancing against the increased risk for bleeding. However, the level of evidence is low and there is still uncertainty about the optimal peri-and postprocedural antithrombotic treatment regimen after TAVR, in particular in patients with concurrent AF.…”
Section: Introductionmentioning
confidence: 99%